Embryo loss and double effect. Issue 8 (3rd January 2013) - Di Nucci, Ezio
Abstract : I defend the argument that if embryo loss in stem cell research is morally problematic, then embryo loss in in vivo conception is similarly morally problematic. According to a recent challenge to this argument, we can distinguish between in vivo embryo loss and the in vitro embryo loss of stem cell research by appealing to the doctrine of double effect. I argue that this challenge fails to show that in vivo embryo loss is a mere unintended side effect while in vitro embryo loss is an intended means and that, even if we refine the challenge by appealing to Michael Bratman's three roles of intention, the distinction is still unwarranted.